OC-093 The Effects of Faecal Microbiota Transplantation on the Innate Immune System and Epithelial Tight Junction Expression in Chronic Refractory Pouchitis. (4th June 2013) - Landy, J; Al-Hassi, H O; Mann, E R; Peake, S T; McLaughlin, S D; Perry-Woodford, Z L; Ciclitira, P J; Nicholls, J; Clark, S K; Knight, S C; Hart, A L
Abstract : Introduction: Faecal microbiota transplantation (FMT) may be beneficial in IBD. A durable change in recipients' microbiota following FMT has been demonstrated. No previous study has assessed the immunological effects of FMT. We aimed to assess the immunological effects of FMT in patients with chronic refractory pouchitis. Methods: FMT was performed via nasogastric tube. Mucosal biopsies samples were collected at pouchoscopy from eight patients with chronic refractory pouchitis before and four weeks after FMT. The epithelium was identified following incubation with EDTA and lamina propria dendritic cells (DCs) were identified following collagenase digestion. Epithelial cells were identified as pancytokeritin positive cells and expression of ZO-1, claudin 1 and claudin 2 were measured by multicolour flow cytometry. DC were identified as an HLA DR+, lineage- (CD3-, CD14-, CD16-, CD19-, CD34-) population. Expression of TLR 2, 4 and 5, β7 and CCR 9, and CD40 were measured by multicolour flow cytometry. Cytokines were assessed by multiplex ELISA of biopsy supernatants. The t-test was used in statistical analysis. Results: There was a tendency for increased expression of claudin 2 (18.6% +- 11.4% v 39.6% +-13.4%, p = 0.3). Lower levels in lamina propria DC expression of TLR4(45.8% +- 6.5% v 33.6% +- 6.9%) and TLR 5(35.5% +-12.2% v 23.3% +-11.5%) as well as β7 expression (39.9% +-7.6% v 31.9% +-4.5%) were not statistically significant. There were no changes in the levels of IL2, 4, 6, 10, TNF, IFN or IL17 in the supernatant of mucosal biopsies before or 4 weeks after FMT. However, a rise in IL10 (9.1pg/ml +-1.2 v 12.5pg/ml +-2.9, p = 0.2) was noted following FMT. Conclusion: There were no significant alterations in epithelial tight junction expression or immunological factors studied following FMT. In chronic refractory pouchitis, faecal transplantation may not be effective in altering the aberrant immunological response. Disclosure of Interest: None Declared